The Barriers of using Education Technology for Optimizing the Educational Experience of Learners (Global Journal of Management and Business Research, 2014)
The paper will discuss the impact that education technology has on the teacherstudent experience. Does learning really take place or has the educator been removed from the teaching experience and environment and does this impact on the learning environment. The study will conclude that technology can enhance the teacher-student experience; although the educator-student learning experience cannot be replaced by technology, due to human and social elements which technology lacks. Education technology does not have interpersonal interaction and an increase in technology can lead to less interest within teacher-student relations. Communication constitutes of 80% of verbal communication through language, while 20 percent is nonverbal such as writing. The various types of education technology used in the teaching process falls into the 20 percent category which is nonverbal and can be ineffective and based on research if used alone is not the most effective tool for teaching and learning.
Keywords: barriers; educational change education technology; instructional; technology; teacher learner education; teaching and learning technology integration